Sequenced genomes and rapidly emerging technologies pave the way for conifer evolutionary developmental biology - Uddenberg, Daniel; Akhter, Shirin; Ramachandran, Prashanth; Sundström, Jens F.; Carlsbecker, Annelie (Frontiers in Plant Science, 2015)
Conifers, Ginkgo, cycads and gnetophytes comprise the four groups of extant gymnosperms holding a unique position of sharing common ancestry with the angiosperms. Comparative studies of gymnosperms and angiosperms are the key to a better understanding of ancient seed plant morphologies, how they have shifted over evolution to shape modern day species, and how the genes governing these morphologies have evolved. However, conifers and other gymnosperms have been notoriously difficult to study due to their long generation times, inaccessibility to genetic experimentation and unavailable genome sequences. Now, with three draft genomes from spruces and pines, rapid advances in next generation sequencing methods for genome wide expression analyses, and enhanced methods for genetic transformation, we are much better equipped to address a number of key evolutionary questions relating to seed plant evolution. In this mini-review we highlight recent progress in conifer developmental biology relevant to evo-devo questions. We discuss how genome sequence data and novel techniques might allow us to explore genetic variation and naturally occurring conifer mutants, approaches to reduce long generation times to allow for genetic studies in conifers, and other potential upcoming research avenues utilizing current and emergent techniques. Results from developmental studies of conifers and other gymnosperms in comparison to those in angiosperms will provide information to trace core molecular developmental control tool kits of ancestral seed plants, but foremost they will greatly improve our understanding of the biology of conifers and other gymnosperms in their own right.